Tyrosine kinases Lyn and Syk regulate B cell receptor-coupled Ca2+ mobilization through distinct pathways. - Takata, M (1994)
Stimulation of B lymphocytes through their antigen receptor (BCR) results in rapid increases in tyrosine phosphorylation on a number of proteins and induces both an increase of phosphatidylinositol and mobilization of cytoplasmic free calcium. The BCR associates with two classes of tyrosine kinase: Src-family kinase (Lyn, Fyn, Blk or Lck) and Syk kinase. To dissect the functional roles of these two types of kinase in BCR signaling, lyn-negative and syk-negative B cell lines were established. Syk-deficient B cells abolished the tyrosine phosphorylation of phospholipase C-gamma 2, resulting in the loss of both inositol 1,4,5-trisphosphate (IP3) generation and calcium mobilization upon receptor stimulation. Crosslinking of BCR on Lyn-deficient cells evoked a delayed and slow Ca2+ mobilization, despite the normal kinetics of IP3 turnover. These results demonstrate that Syk mediates IP3 generation, whereas Lyn regulates Ca2+ mobilization through a process independent of IP3 generation.